PELATIHAN AKUNTANBILITAS DAN PENGELOLAAN KEUANGAN MASJID DI MASJID AL-MUSLIMIN, MEDAN - Ikhwan Lubis; M. Sianturi; AM Hatuaon Sihite; Edizal Hatmi; Ilhamsyah Ilhamsyah (BADAN PENERBIT STIEPARI PRESS, 2022)
This study aims to find out that the administrators of Masjid Al Muslimin' carry out accounting practices and Islamic theology correctly. About how mosque administrators disclose and report all activities related to mosque financial management and whether mosque administrators carry out the management of mosque finances in an accountable manner to worshippers. This type of research uses a qualitative type of research. The type of data used in this study was primary data obtained directly with the speakers, namely the mosque administrators and worshippers of Masjid Al Muslimin'. Data sources are derived from interviews, documentation, and observations. The analysis technique used is Logic Analytic, which is to adjust various observations with interviews with the theories used in this study. The results of this study the accounting practices used in Masjid Al Muslimin' are very simple but the administrators really maintain the mandate that has been given by the pilgrims to manage the mosque finances well to the administrators. Although the pilgrims have great confidence in the administrators, in practice the administrators are still accountable (accountability) with what is done and open (transparency) in terms of delivery and recording. In addition, the rule of law of islamic teachings must be the standard basis for carrying out accountability.